2000
DOI: 10.1046/j.1365-2419.2000.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of minke whales in the Bellingshausen and Amundsen Seas (60°W–120°W), with special reference to environmental/physiographic variables

Abstract: The relationship between the distribution of minke whales (Balaenoptera acutorostrata) in the Bellingshausen and Amundsen Seas (longitude between 60°W and 120°W), and environmental and physiographic variables (sea‐surface temperature, sea‐ice extension, and sea‐floor‐slope type), was studied to determine whether these environmental and physical factors affect the distribution and density of minke whales. The analysis was based on sightings data obtained from the 1989/90 and 1982/83 IWC/IDCR cruises. The mean s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 26 publications
2
32
1
Order By: Relevance
“…However, due to problems of low sample size of data, few significant patterns or correlations have been observed. Kasamatsu et al (2002) managed to show strong correlations between the presence Antarctic minke whales (B. bonaerensis) and ice edges areas in the Bellinghausen and Amundsen Seas in the Antarctic. Although no significant correlations were found between minke whale density and sea surface temperature, it was observed that densities appeared to be higher during the surveys conducted during 1982/1983 when the region was experiencing intrusions of colder water (Kasamatsu et al, 2002).…”
Section: Discussionmentioning
confidence: 94%
“…However, due to problems of low sample size of data, few significant patterns or correlations have been observed. Kasamatsu et al (2002) managed to show strong correlations between the presence Antarctic minke whales (B. bonaerensis) and ice edges areas in the Bellinghausen and Amundsen Seas in the Antarctic. Although no significant correlations were found between minke whale density and sea surface temperature, it was observed that densities appeared to be higher during the surveys conducted during 1982/1983 when the region was experiencing intrusions of colder water (Kasamatsu et al, 2002).…”
Section: Discussionmentioning
confidence: 94%
“…Certainly factors such as water depth, sea bottom sediment and even the extent of sea ice have all been shown to influence minke distributions across a range of different habitats (e.g. Kasamatsu et al 2000a;Naud et al 2003;Macleod et al 2004;Cecchetti 2006), but the interplay between these different factors evidently varies from one geographic region to the next (Tetley April 2007). Consequently fluctuations in both fine and large-scale physiography are believed to be significant for the distribution of minke whales within the Moray Firth, and thus a greater understanding of their habitat preferences in this region is considered to be important not only for the improvement of abundance estimates and interpretations of population trends here, but also for the establishment of protected areas for the long-term coastal management of the species in these waters.…”
Section: Introductionmentioning
confidence: 99%
“…Studies concerning whales in the Antarctic have largely been limited to describing distribution patterns in relation to large scale oceanographic features (Uda 1954, Tynan 1998 or coarse surveys of prey across broad spatial scales (Kasamatsu et al 2000a,b, Nicol et al 2000, Reid et al 2000, Murase et al 2002. Such relationships have not been assessed at smaller spatial extents (10s of km) (Thiele et al 2004).…”
Section: Introductionmentioning
confidence: 99%